The selective oestrogen receptor modulator, bazedoxifene, mimics the neuroprotective effect of 17β‐oestradiol in diabetic ischaemic stroke by modulating oestrogen receptor expression and the MAPK/ERK1/2 signalling pathway. (19th June 2019) - Burguete, María C.; Jover‐Mengual, Teresa; López‐Morales, Mikahela A.; Aliena‐Valero, Alicia; Jorques, María; Torregrosa, Germán; Alborch, Enrique; Castelló‐Ruiz, María; Salom, Juan B.
Abstract: Because neuroprotection in stroke should be revisited in the era of recanalisation, the present study analysed the potential neuroprotective effect of the selective oestrogen receptor modulator, bazedoxifene acetate (BZA), in an animal model of diabetic ischaemic stroke that mimics thrombectomy combined with adjuvant administration of a putative neuroprotectant. Four weeks after induction of diabetes (40 mg kg ‐1 streptozotocin, i.p.), male Wistar rats were subjected to transient middle cerebral artery occlusion (intraluminal thread technique, 60 minutes) and assigned to one of three groups treated with either: vehicle, BZA (3 mg kg ‐1  day ‐1, i.p.) or 17β‐oestradiol (E2 ) (100 μg kg ‐1  day ‐1, i.p.). At 24 hours post‐ischaemia‐reperfusion, brain damage (neurofunctional score, infarct size and apoptosis), expression of oestrogen receptors (ER)α, ERβ and G protein‐coupled oestrogen receptor), and activity of the mitogen‐activated protein kinase/extracellular signal‐regulated kinase (MAPK/ERK)1/2 and phosphoinositide 3‐kinase/Akt pathways were analysed. At 24 hours after the ischaemic insult, both BZA‐ and E2 ‐treated animals showed lower brain damage in terms of improved neurofunctional condition, decreased infarct size and decreased apoptotic cell death. Ischaemia‐reperfusion induced a significant decrease in ERα and ERβ expression without affecting that of G protein‐coupled oestrogen receptor, whereas BZA and E2 reversed such a decrease. The ischaemic insult up‐regulated the activity of both the MAPK/ERK1/2 and phosphoinositide 3‐kinase/Akt pathways; BZA and E2 attenuated the increased activity of the ERK1/2 pathway, without affecting that of the Akt pathway. The results of the present study lend further support to the consideration of BZA as an effective and safer alternative overcoming the drawbacks of E2 with respect to improving diabetic ischaemic stroke outcome after successful reperfusion.